Durability and doses of organic colorant in the visual quality of bermudagrass Discovery TM - Matheus Vinícios Leal Nascimento; Patrick Luan Ferreira dos Santos; João Victor Costa; Juliana Trindade Martins; Roberto Lyra Villas Bôas; Leandro José Grava de Godoy (Ornamental Horticulture, 2020)
The painting of sports turf with colorants is a common practice, having as main objective, the maintenance of the aesthetic aspect of the grass, in order to maximize the aesthetic quality. colorants are used to provide green color to grasses during periods of stress and numbness and are considered an alternative to warm weather grasses during the winter months. The recent popularity of colorants has occurred due to water conservation efforts as well as reduced costs of operations compared to winter "overseeding" sowing values. Due to the current interest in the use of lawn colorant and the scarcity of information on this topic, the objective was to evaluate the durability and doses of organic colorant in the visual quality of Discovery TM bermudagrass. The experiment was installed in the field, subdivided into plots of bermudagrass Discovery TM, being the treatments: T1 - 0 ml L-1 (Witness), T2- 33 ml L-1, T3- 50 ml L-1, T4- 66.6 ml L-1 (manufacturer's recommendation), T5- 83 ml L-1, T6- 100 ml L-1 of commercial organic lawn specific colorant. Every 10 days the indices of green staining, reflectance, vegetation by normalized difference (NDVI) and digital image were evaluated. The results indicated doses between 66.6 and 83.3 ml L-1 and those recommended, given the durability of the product. The reflectance indices were accurate in estimating the nutritional status of the grass even after application of the colorant, while evaluations by digital image give a false impression that the grass is well nourished.